The time course of physiological adaptations made during altitude training
Initially at altitude there is a 5% loss in endurance capacity. The first four days exhibit a transition phase when workloads and quality are noticeably affected. This is followed by an adjustment phase where training performances improve. Within 12 days the energy systems are enhanced and performances return to typical sea-level response characteristics. After the adjustment serious training can be entertained and training improvements can be expected (enhancement phase). Implications: These time estimates are general and vary considerably between individuals. The response patterns of swimmers are similar, it is the time spent in each phase that differs. For elite performers, it is unlikely that times recorded at sea level will be matched at altitude, certainly in training sets that require primarily aerobic work and in race distances of 200 m and longer. (ICAR 1990-91 Report)